Justice and conservation: The need to incorporate recognition. (May 2016) - Martin, Adrian; Coolsaet, Brendan; Corbera, Esteve; Dawson, Neil M.; Fraser, James A.; Lehmann, Ina; Rodriguez, Iokiñe
Abstract: In light of the Aichi target to manage protected areas equitably by 2020, we ask how the conservation sector should be incorporating concerns for social justice. We focus in particular on 'recognition', because it is the least well understood aspect of environmental justice, and yet highly relevant to conservation because of its concern with respect for local knowledge and cultures. In order to explore the meaning of recognition in the conservation context, we take four main steps. First, we identify four components of recognition to serve as our analytical framework: subjects of justice, the harms that constitute injustice, the mechanisms that produce injustices, and the responses to alleviate these. Secondly, we apply this framework to explore four traditions of thinking about recognition: Hegelian intersubjectivity, critical theory, southern decolonial theory, and the capabilities approach. Thirdly, we provide three case studies of conservation conflicts highlighting how different theoretical perspectives are illustrated in the claims and practices of real world conservation struggles. Fourthly, we finish the paper by drawing out some key differences between traditions of thinking, but also important areas of convergence. The convergences provide a basis for concluding that conservation should look beyond a distributive model of justice to incorporate concerns for social recognition, including careful attention to ways to pursue equality of status for local conservation stakeholders. This will require reflection on working practices and looking at forms of intercultural engagement that, for example, respect alternative ways of relating to nature and biodiversity. Highlights: Conservation justice is intrinsically desirable and can also support effectiveness. Distribution alone will not achieve conservation justice, recognition is also needed. Conservation provides opportunities for recognition of marginalised peoples. But also threats. We can incorporate recognition through methods that promote stakeholder equality.